French rural sociology: from specialization to a transversal sociological approach - Debroux, Josette; Matuchniak-Mystkowska, Anna; Starosta, Paweł (Sociology of rural worlds in Poland and France: field research and studies, 2024)
After the Second World War, in the context of expansion of social sciences and along with a construction of a ‘social demand’, French rural sociology emerged as a specialization based on an opposition between the urban and the rural, and a presupposition that the latter is highly specific and distinct. The theory of peasant societies has accompanied a transformation of the peasantry and a redefinition of its place in the French society. This theory does not make it possible to understand the changes that have taken place since the year 1975, in particular an increased mobility between urban and rural areas, a decline of the farming population which has evidently become a minority in most rural areas, and transformations in agriculture.  Disappearance of rural sociology at the institutional level, which took place at the end of the 1970s, did not mean the end of research on the rural world. While some projects followed in the wake of rural sociology of the 1960s and 1970s, others were conducted by a new generation of sociologists who had not been trained in 'rural sociology', with its presuppositions and specific concepts. Their approach to rural areas fit in the fields of sociology in which they work (political sociology, economic sociology, sociology of gender, sociology of socialization...), although this does not rule out the view that 'rural areas', despite their diversity, maintain certain specific features.